2015
DOI: 10.1073/pnas.1418702112
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deposition of oxidized biogenic compounds to a temperate forest

Abstract: We report fluxes and dry deposition velocities for 16 atmospheric compounds above a southeastern United States forest, including: hydrogen peroxide (H 2 O 2 ), nitric acid (HNO 3 ), hydrogen cyanide (HCN), hydroxymethyl hydroperoxide, peroxyacetic acid, organic hydroxy nitrates, and other multifunctional species derived from the oxidation of isoprene and monoterpenes. The data suggest that dry deposition is the dominant daytime sink for small, saturated oxygenates. Greater than 6 wt %C emitted as isoprene by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
433
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(469 citation statements)
references
References 106 publications
24
433
4
Order By: Relevance
“…Based on back-trajectories, the most probable transport time from the city to the measurement site was between 4 h and 5 h. By comparison, (4, 3)-ISOPOOH, isoprene, (1, 2)-ISOPOOH, MACR, and MVK have characteristic lifetimes to OH loss of ∼2 h, 3 h, 4 h, 10 h, and 14 h, respectively, for a reference OH concentration of 10 6 cm −3 typical of many environments. Deposition and entrainment can also be important loss mechanisms (26,27). Background air, meaning the Amazon basin in the nominal absence of the pollution plume of Manaus, had significant variability associated with it, especially with respect to effective photochemical age.…”
Section: Significancementioning
confidence: 99%
“…Based on back-trajectories, the most probable transport time from the city to the measurement site was between 4 h and 5 h. By comparison, (4, 3)-ISOPOOH, isoprene, (1, 2)-ISOPOOH, MACR, and MVK have characteristic lifetimes to OH loss of ∼2 h, 3 h, 4 h, 10 h, and 14 h, respectively, for a reference OH concentration of 10 6 cm −3 typical of many environments. Deposition and entrainment can also be important loss mechanisms (26,27). Background air, meaning the Amazon basin in the nominal absence of the pollution plume of Manaus, had significant variability associated with it, especially with respect to effective photochemical age.…”
Section: Significancementioning
confidence: 99%
“…It has been reported that the heterogeneous reaction is the most important sink for H 2 O 2 in urban (Liang et al, 2013b) and suburban areas (Guo et al, 2014). In contrast, OH-initiated reaction and dry deposition were regarded as the major removal pathways of organic peroxides in rural and forests areas (Nguyen et al, 2015). Here, heterogeneous uptake by aerosols turned out to be the predominant sink for atmospheric peroxides in the NCP, accounting for more than 60 % of the total loss, while dry deposition became the marginal removal pathway that contributed ∼ 10 % to the destruction of H 2 O 2 , MHP and PAA.…”
Section: Heterogeneous Uptake Of Peroxides By Aerosolmentioning
confidence: 96%
“…and 1.0 × 10 −5 s −1 , respectively at the PBL height of 1 km (Zhang et al, 2003;Emmerson et al, 2007;Lu et al, 2012;Guo et al, 2014;Liu et al, 2015;Nguyen et al, 2015). The PBL height over Wangdu during this campaign was derived from the hybrid single-particle lagrangian integrated trajectory (HYSPLIT) model (Draxler and Rolph, 2012), which varied between about 300 m at midnight and over 3000 m at noon.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these dummy 15 species will not participate in any further chemical reaction, their precursors are effectively removed from the model chemical scheme. The deposition velocities of peroxides, formic and nitric acid are based on (Nguyen et al, 2015) while those for PINAL and PAN are based on (Evans et al, 2000) using the average of the deposition rates for water, forest and grass. The model scheme is included in the supplementary of this manuscript.…”
Section: The Caaba/mecca Modelmentioning
confidence: 99%